Solid phase concentrations in the sediment at 5 sites along a water depth transect in the Gulf of Mexico (Louisiana continental shelf) - Wytze K Lenstra (PANGAEA, 2022)
All sediments were freeze-dried and the porosity was determined from the weight loss upon freeze drying. To determine the total elemental concentrations of aluminum (Al), Co, Fe, Mn, Ni, and S, ca. 125 mg of sediment was digested in 2.5 ml mixed acid (HNO3:HClO4; 2:3) and 2.5 ml 40% HF at 90?C. After fuming off the acids, the residue was redissolved in 4.5% HNO3. The solutions were subsequently analyzed on an ICP-OES. The analytical uncertainty based on duplicates and triplicates was <1% for Al, <4.2% for Co, <1.6% for Fe, <2.5% for Mn, <2.3% for Ni, and <1.7% for S. A subsample of circa 300 mg was decalcified with 2 wash steps of 1M HCl and subsequently dried, powdered and analyzed for carbon (C) using an elemental analyser (Fisons Instrumentsmodel NA 1500 NCS). Organic C content was determined after correction for the weight loss following decalcification. The analytical uncertainty based on duplicates and triplicates was <0.07 wt%.